Unmasking The Impostor: Myxoid Liposarcoma Of The Arm Masquerading As A Spindle Cell Lesion – A Rare Case Report - Atri, Kanak; Goel, Seema; Verma, Atul; Devra, Anshu Gupta Devra4 (Journal of Neonatal Surgery, 2025)
BACKGROUND: Myxoid liposarcoma (MLPS) is a malignant tumour composed of uniform, round to ovoid cells with variable numbers of small lipoblasts, set in a myxoid stroma with arborizing vasculature. MLPS typically present within deep soft tissues of the extremities, often thigh and rarely from the upper extremities, subcutis or retroperitoneum. MLPS accounts 20-30% of liposarcoma and 5% of adult soft tissue sarcomas with a peak incidence in the fourth to fifth decades. CASE REPORT: We present a case of 23 years old female with sudden onset painful right arm swelling. MRI right arm was suggestive of vascular lesion while MRI with contrast suggested it was a neurogenic tumor. Cytology findings suggested a mesenchymal lesion, with uncertain malignant potential. The histopathological and immunohistochemical findings were suggestive of Adipocytic tumor - Likely Myxoid Liposarcoma (FNCLCC Grade 2). CONCLUSION: The case highlights the importance of including myxoid liposarcoma (MLPS) in the differential diagnosis of spindle cell lesions, especially when imaging and cytological findings are ambiguous. A multidisciplinary approach is essential for accurate diagnosis. Early detection of MLPS enables prompt treatment, ultimately improving patient prognosis and outcomes.